Young adults' perceptions of breastfeeding in public: a focus group study - Yip Ka-Huen; Yip Yuk-Chiu; Lee Catherine Man-Yin; Siu Mei-Yi; Ngai Shu-Ying; Chow Mei-Kuen (Sciendo, 2020)
To elucidate the perceptions of young Chinese adults aged 18-25 toward adopting breastfeeding in public in Hong Kong Special Administrative Region (Hong Kong), China.